Enhanced MRC for decode-and-forward cooperative diversity systems - Nasri, Amir; Schober, Robert; Uysal, Murat (IEEE Transactions on Wireless Communications, 2012)
In this letter, we propose a novel enhanced maximalratio combining (EMRC) scheme for multibranch decodeandforward (DF) cooperative diversity systems consisting of a source, a destination, and multiple relays. This scheme employs adjustable parameters at the relays and the destination which enable this scheme to appropriately adapt to variations in the sourcerelay and relaydestination channel gains. For the proposed EMRC scheme, we analyze the asymptotic error rate performance for high signaltonoise ratios and Rayleigh fading. Based on the obtained analytical expressions, we find the optimal parameters that lead to minimization of the asymptotic error rate. Furthermore, we compare the error rate performance as well as the feedback overhead of EMRC with those of important DF schemes, namely, cooperative MRC (CMRC) and two DF schemes based on the link adaptive regeneration (LAR) concept, namely, LARα inst and LAR. We show that although the feedback requirements of EMRC are similar to those of LAR, EMRC achieves a performance similar to that of LARα inst, which has a substantially higher feedback overhead. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative diversity; cooperative maximal - ratio combining; decode - and - forward; link adaptive regeneration; performance analysis and optimization